The Relationship Between the Change of Parathyroid Hormone Level in Patients Under Bisfosfonates Treatment and DXA - Ferda Özdemir; Derya Demirbağ Kabayel; Esra Esen; Dilek Kurtoğlu (Archives of Rheumatology, 2006)
Objective: We aimed to investigate the relationship between the level of parathyroid hormone (PTH) and T score obtained by Dual energy X-ray absorptiometry (DXA) in patients with diagnosed and treated as postmenopausal and senile osteoporosis in our osteoporosis (OP) clinic. We also evaluated the evaluation of the difference between dressing styles and changes of PTH level according to season in these patients. Patients and Methods: In this retrospective study, the patients who were administered bisphosphonat as antiresorptive treatment as well as calcium and Vit D were chosen, after the scanning of 1625 patients. Inclusion criteria were a) had normal level of PTH values before treatment, b) had no systemic disease to cause high PTH level. Demographic characteristics of the patients, PTH and T scores of lomber spine and hip measured by DXA were recorded at the beginning and after one year treatment. At the second evaluation after one year treatment, 47 patients who had increased PTH levels were named as the first group and 52 patients who had normal PTH levels were named as the second group. T scores of both groups were compared. Results: In pre-treatment period, no difference was found between the PTH levels and T scores of both groups. A statistically significant difference was found between DXA evaluations carried out at the beginning and one year after the treatment. However, when the groups were compared with each other, no difference was found between the DXA values recorded one year later. Conclusion: It was concluded that high PTH levels in patients with OP has no effect on DXA values, which may result from the protective effect of the regular treatment in patients with OP. (Rheumatism 2006; 21: 91-4)